2019
DOI: 10.3389/fimmu.2019.01658
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Gestational IL-13 During Fetal Development Is Associated With Hyperactivity and Inattention in Eight-Year-Old Children

Abstract: Maternal immune activation (MIA) during fetal development leads to behavioral and psychological disorders in the offspring. Concomitantly, insufficient supply of polyunsaturated fatty acids (PUFAs) is suspected to contribute to early neuronal maldevelopment due to the immune modulatory capabilities of PUFAs. However, human data are missing considering both of these aspects and their impact on children's behavioral outcomes. In line, this study aimed to elucidate the influence of gestational cytokines and PUFA-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
0
11
1
Order By: Relevance
“…In our study, however, we observed no differences in maternal or cord blood cytokines between children with and without eczema, nor between children with and without ADHD symptoms. Our findings are contrary to results reported by other studies ( 36 , 37 ). A possible reason for the different results may be that we assayed cord blood without stimulation and cord blood levels of IFNγ without stimulation are generally low ( 38 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, however, we observed no differences in maternal or cord blood cytokines between children with and without eczema, nor between children with and without ADHD symptoms. Our findings are contrary to results reported by other studies ( 36 , 37 ). A possible reason for the different results may be that we assayed cord blood without stimulation and cord blood levels of IFNγ without stimulation are generally low ( 38 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Another reason for the absence of differences in maternal or cord cytokines between children with and without eczema, nor between children with and without ADHD symptoms that we observed may be due to limited immune profiling. While the Newborn Epigenetics Study and LINA cohort reported associations between maternal IL-12p70, IL-17A, IL-1β, and IL-13 levels and child neurodevelopment ( 36 , 37 ), we did not measure these cytokines. We also assayed cytokines from maternal blood during pregnancy and cord blood which is not indicative of subsequent inflammation that may be brought about by gut microbiome dysbiosis that we have observed in children with eczema as well as in children with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the complex cascade of changes associated with maternal infection and the subsequent maternal immune response ( 7 ) is uniquely positioned to influence the developing fetal brain. Even in the absence of an acute inflammatory event triggered by infection, variation in maternal cytokine levels during pregnancy have been associated with offspring neurobehavioral outcomes, including early alterations in brain growth, functional connectivity, behavioral development ( 8 , 9 , 10 , 11 , 12 ), and long-lasting dysregulation of stress response circuitry ( 13 ). Collectively, these studies suggest that changes in maternal-fetal immune environment during pregnancy can have long-lasting consequences, ranging from subtle differences in offspring brain and behavioral development to severe NDDs.…”
Section: Maternal Infection and Offspring Neurodevelopmentmentioning
confidence: 99%
“…In this context, the type of biological matrix elected to measure cytokine concentrations as proxies for immune activity at birth is critical. Most studies have relied on DBS collected from the neonate several hours or days after birth ( Abdallah et al., 2013 ; Ghassabian et al., 2018 ; Heuer et al., 2019 ; Krakowiak et al., 2017 ; Mizejewski et al., 2013 ; Nelson et al., 2006 ; Skogstrand et al., 2019 ; Thürmann et al., 2019 ; Zerbo et al., 2014 ). In contrast, we have measured cytokine levels in CBS, i.e.…”
Section: Discussionmentioning
confidence: 99%